Muslims in the Enlarged Europe : Religion and Society - Allievi, Stefano; Dassetto, Felice; Marechal, Brigitte; Nielsen, Jørgen (Brill Book Archive Part 1, ISBN: 9789004472495., 2003)
This volume describes the main characteristics of contemporary European Islam. Following an outline of the historical background and some statistics related to the presence of Islam in Europe, the process of growth/ the development of Islam is analysed through religious instruction in educational systems, organisational structures and the forms of political participation by Muslims. In addition to a description of the relationship between European states and Islam in judicial terms, the different types of the inclusion/integration of Islam in European society is studied by looking at the media, the relations between religions, economic and international dimensions, and the manner in which views have changed following the events of September 11. Based on extensive bibliographal research, field studies and specific contributions of scholars, this book provides a rare and useful overall review for a wide public. Muslims in the Enlarged Europe has been selected by Choice as Outstanding Academic Title (2005).